2018
DOI: 10.1080/09540091.2018.1443318
|View full text |Cite
|
Sign up to set email alerts
|

Improving interactive reinforcement learning: What makes a good teacher?

Abstract: Interactive reinforcement learning has become an important apprenticeship approach to speed up convergence in classic reinforcement learning problems. In this regard, a variant of interactive reinforcement learning is policy shaping which uses a parent-like trainer to propose the next action to be performed and by doing so reduces the search space by advice. On some occasions, the trainer may be another artificial agent which in turn was trained using reinforcement learning methods to afterward becoming an adv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Figure 1 shows the IntRL approach with an advisor observing the learning process and providing advice in selected episodes. While the human-in-the-loop approach to learning is one of the interactive agent’s greatest strength, the human can also often be the biggest obstacle [ 16 ]. Moreover, human trials are expensive, time-consuming, suffer from issues with repeatability, and acquisition of participants can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the IntRL approach with an advisor observing the learning process and providing advice in selected episodes. While the human-in-the-loop approach to learning is one of the interactive agent’s greatest strength, the human can also often be the biggest obstacle [ 16 ]. Moreover, human trials are expensive, time-consuming, suffer from issues with repeatability, and acquisition of participants can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A bad teacher can negatively influence the learning process and somehow limit the learner by teaching a strategy that is not necessarily optimal. To select a good teacher, it is necessary to take into account that an agent that obtains the best results for the task, in terms of accumulated reward, is not necessarily the best teacher [27]. Instead, a good teacher could be one with a small standard deviation over the visited states.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the given advice by the external trainer must also be considered to improve the learning. It has been shown that inconsistent advice may be very detrimental during the learning process, so that in case of low consistency of advice, autonomous learning may lead to better performance [27].…”
Section: Agent External Trainermentioning
confidence: 99%
“…Torrey and Taylor ( 2013 ) report that different ways of advising, such as early, importance, mistake correcting, and predictive advising may become beneficial when teaching on a budget. Cruz et al ( 2018a ) studied which types of advisors are most beneficial during learning of the agent in a simulated domestic scenario.…”
Section: Related Workmentioning
confidence: 99%